Research on Energy Saving and Comfort Capability of Train Variable-frequency Air Conditioner - SU Ci; WANG Shenyu; WU Shuanghu; MENG Fanhua; MA Hongfu (机车电传动)
Principle and control method of variable-frequency air conditioner were introduced, and capabilities of energy saving and comfort about variable-frequency and fix-frequency air conditioner were researched. The results showed that compared with fixfrequency air conditioner, variable-frequency air conditioner not only saved energy, but also had better temperature control precision and comfort.